Validation of an e-health readiness assessment framework for developing countries - Kabelo Leonard Mauco; Richard E. Scott; Maurice Mars (BMC, 2020)
Abstract Background Studies document e-health as having potential to improve quality of healthcare services, resulting in both developed and developing countries demonstrating continued interest in e-health uptake and use. e-Health implementations are not always successful as high failure rates have been reported in both developed and developing countries. These failures are often a result of lack of e-health readiness. e-Health readiness has been defined as the preparedness of healthcare institutions or communities for the anticipated change brought by programs related to information and communication technologies. As such it is critical to conduct an e-health readiness assessment prior to implementation of e-health innovations so as to reduce chances of project failure. Noting the absence of an adequate e-health readiness assessment framework (eHRAF) suitable for use in developing countries, the authors conceptualised, designed, and created a developing country specific eHRAF to aid in e-health policy planning. The aim of this study was to validate the developed eHRAF and to determine if it required further refinement before empirical testing. Methods Published options for a framework validation process were adopted, and fifteen globally located e-health experts engaged. Botswana experts were engaged using saturation sampling, while international experts were purposively selected. Responses were collated in an Excel spreadsheet, and NVivo 11 software used to aid thematic analysis of the open ended questions. Results Analysis of responses showed overall support for the content and format of the proposed eHRAF. Equivocal responses to some open ended questions were recorded, most of which suggested modifications to terms within the framework. One expert from the developed world had alternate views. Conclusions The proposed eHRAF provides guidance for e-health policy development and planning by identifying, in an evidence based manner, the major areas to be considered when preparing for an e-health readiness assessment in the context of developing countries.